Efektifitas penggunaan video sebagai media pembelajaran untuk siswa sekolah dasar - Fernandita Ardhianti (ARKA INSTITUTE, 2022)
The monotonous learning process using books makes it easy for students to feel bored in learning. It is not surprising that many students are sometimes still confused about the material that has been reviewed. In this increasingly advanced era, researchers use the Iyoutube I video media as a medium that can help motivate students to be enthusiastic in the learning process. The purpose of this study is that researchers want to know the effectiveness of video media as a media aid in learning. This researcher uses a qualitative descriptive research method by observing and distributing questionnaires filled out by students. The results showed that students were more enthusiastic when the learning process used youtube video media. So that the learning process using youtube videos is proven to be able to motivate students for the learning process.